The Nexus of ESG Score and Stock Return: Evidence from The LQ45 Index - Prayogo, Syamsi Mustofa Singgih; Wisnoentoro, Rizky (Indonesian Journal of Sustainability Accounting and Management, 2024)
The objective of this study is to examine the relationship between Environmental, Social, and Governance (ESG) aspects and the return on stock performance in Indonesia. An exhaustive examination of the data from the Indonesian stock market LQ45 Index is undertaken to determine the firms that give priority to environmental, social, and governance (ESG) policies. The study utilizes a quantitative methodology, employing cross-sectional dependency test with the sample of 45 blue chip firms. Breusch- Godfrey Serial Correlation LM Test and Heteroscedasticity Test were used in the research. This study enhances the current body of literature by offering empirical proof about the influence of ESG score on stock returns, particularly within the framework of the LQ45 index. The results will underscore the importance of ESG considerations for investors and stress the possible financial advantages of integrating ESG elements into investing strategies. This study contributes to the expanding pool of information on sustainable investment and its ramifications for financial markets.